Respostas
respondido por:
12
2c + 3g =17
c - g = 1
multiplicando a 2ª equação por "3" e somando com a 1ª equação
2c + 3g = 17
3c - 3g = 3
⇒ 5c = 20
c = 20/5 ⇒ c = 4
substituindo "c" na 1ª equação
2(4) + 3g = 17
3g = 9
g = 9/3 ⇒ g = 3
Resposta: c = 4 g = 3
c - g = 1
multiplicando a 2ª equação por "3" e somando com a 1ª equação
2c + 3g = 17
3c - 3g = 3
⇒ 5c = 20
c = 20/5 ⇒ c = 4
substituindo "c" na 1ª equação
2(4) + 3g = 17
3g = 9
g = 9/3 ⇒ g = 3
Resposta: c = 4 g = 3
vitoriaregina8:
e como eu resolvo essa? m + c = 20 2m + 4c = 54
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás